Grain size distribution after similar and dissimilar gas tungsten arc welding of a ferritic stainless steel - Ranjbarnodeh, Eslam (Journal of Mining and Metallurgy, Section B: Metallurgy, 2015)
In this study, gas tungsten arc welding of ferritic stainless steel and grain size distribution in heat affected zone of the welded samples were investigated. Both similar and dissimilar arc welding operations were considered where in dissimilar welding joining of stainless steel to mild steel was examined. In the first stage, a three-dimensional model was developed to evaluate temperature field during and after arc welding while the model was performed using finite element software, ANSYS. Then, the effects of welding heat input and dissimilarity of the joint on the weld pool shape and grain growth in HAZ of stainless steel was investigated by means of model predictions and experimental observations. The results show that the similar joint produces wider HAZ and considerably larger grain size structure while in the dissimilar welds, the low carbon part acts as an effective heat sink and prevents the grain growth in the stainless steel side as well reduces the welding maximum temperature.